A DIFFERENTIAL CATALOG OF RIGHT ASCENTIONS OF 345 RRS2 STARS - Bazej, N. V. (Одеські астрономічні публікації, 2017)
The meridian Repsold circle of Odessa Astronomical Observatory was used for conducting the meridian part of the CGNFOR program in order to establish connection between the radio and optical coordinate systems. Over 6600 differential observations of the program and reference star right ascensions were made in 1990-1993 within 148 nights. From observational results, a catalogue was complied of right ascensions of 345 stars RRS2 for equinox 12000,0 and epoch of observations. The catalogue was sent to Astronomical Observatory of Kiev University for the inclusion in a summary catalogue of stars RRS2.